A New Clevosaurid from the Triassic (Carnian) of Brazil and the Rise of Sphenodontians in Gondwana - Hsiou, Annie S. (2019)
The early evolution of lepidosaurs is marked by an extremely scarce fossil record during the Triassic. Importantly, most Triassic lepidosaur specimens are represented by disarticulated individuals from high energy accretion deposits in Laurasia, thus greatly hampering our understanding of the initial stages of lepidosaur evolution. Here, we describe the fragmentary remains of an associated skull and mandible of Clevosaurus hadroprodon sp. nov., a new taxon of sphenodontian lepidosaur from the Late Triassic (Carnian; 237–228 Mya) of Brazil. Referral to Sphenodontia is supported by the combined presence of a marginal dentition ankylosed to the apex of the dentary, maxilla, and premaxilla; the presence of ‘secondary bone’ at the bases of the marginal dentition; and a ventrally directed mental process at the symphysis of the dentary. Our phylogenetic analyses recover Clevosaurus hadroprodon as a clevosaurid, either in a polytomy with the Late Triassic to Early Jurassic Clevosaurus and Brachyrhinodon (under Bayesian inference), or nested among different species of Clevosaurus (under maximum parsimony). Clevosaurus hadroprodon represents the oldest known sphenodontian from Gondwana, and its clevosaurid relationships indicates that these sphenodontians achieved a widespread biogeographic distribution much earlier than previously thought.